Two cases of fractures in neonates associated with maternofetal vitamin D deficiency - Albertini, F.; Marquant, E.; Reynaud, R.; Lacroze, V. (Archives de pédiatrie : organe officiel de la Société française de pédiatrie, 2019)
Vitamin D supplementation is essential for the entire population, especially during pregnancy and in the pediatric period. We report two case studies of full-term newborns who presented long-bone fractures associated with severe vitamin D deficiency transmitted to them by their mothers, even though maternal supplementation had been implemented according to the existing recommendations. These observations encourage the investigation of neonatal vitamin D deficiency in the presence of long-bone fractures in the absence of traumatic birth and the necessity of reenforcing the means of prevention and the selection of risk groups in order to adjust vitamin D supplementation during pregnancy individually.